Sex Differences Among Participants in the Latin American Stroke Registry. Issue 4 (18th February 2020) - Arauz, Antonio; Serrano, Fabiola; Ameriso, Sebastián F.; Pujol‐Lereis, Virginia; Flores, Alan; Bayona, Hernán; Fernández, Huberth; Castillo, Alejandro; Ecos, Rosa; Vazquez, Jorge; Amaya, Pablo; Ruíz, Angélica; et al.
Abstract : Background: Reports on sex differences in stroke outcome and risk factors are scarce in Latin America. Our objective was to analyze clinical and prognostic differences according to sex among participants in the LASE (Latin American Stroke Registry). Methods and Results: Nineteen centers across Central and South America compiled data on demographics, vascular risk factors, clinical stroke description, ancillary tests, and functional outcomes at short‐term follow‐up of patients included from January 2012 to January 2017. For the present study, all these variables were analyzed according to sex at hospital discharge. We included 4788 patients with a median in‐hospital stay of 8 days (interquartile range, 5–8); 2677 were male (median age, 66 years) and 2111 female (median age, 60 years). Ischemic stroke occurred in 4293: 3686 as cerebral infarction (77%) and 607 as transient ischemic attack cases (12.7%); 495 patients (10.3%) corresponded to intracerebral hemorrhage. Poor functional outcome (modified Rankin scale, 3–6) was present in 1662 (34.7%) patients and 38.2% of women ( P <0.001). Mortality was present in 6.8% of the registry, with 7.8% in women compared with 6.0% in men ( P =0.01). Death and poor functional outcome for all‐type stroke showed a higher risk in female patients (hazard ratio, 1.3, P =0.03; and hazard ratio, 1.1, P =0.001, respectively). Conclusions: A worse functional outcome and higher mortality rates occurred in women compared with men in the LASE, confirming sex differences issues at short‐term follow‐up.